Mutations of the BRCA1 gene in hereditary breast and ovarian cancer in the Czech Republic - Pohlreich, P; Stríbrná, J; Kleibl, Z; Zikán, M; Kalbácová, R; Petruzelka, L; Konopásek, B (Medical principles and practice, 2003)
OBJECTIVE: Mutations in the BRCA1 gene confer a high risk for the development of breast or ovarian cancer. The aim of this study was to establish the frequency and spectrum of BRCA1 mutations in Czech breast or ovarian cancer families. SUBJECTS AND METHODS: We have screened 28 patients with early-onset cancer and 54 patients from risk families for germ-line mutations in BRCA1. All coding exons were analyzed by the protein truncation test (PTT) and the reverse transcription polymerase chain reaction (RT-PCR). Detected variants were characterized by direct sequencing of PCR products. RESULTS: Five distinct deleterious mutations have been identified in six families. All the mutations led to the premature termination of translation. One mutation was detected in a group of 11 (9.1%) patients with early-onset breast cancer. Two mutations were observed in 32 (6.3%) families with a history of breast cancer only. Three mutations were found in 22 (13.6%) families with both breast and ovarian cancer. The 5382insC mutation was the only abnormality detected twice. In addition, two variant transcripts, the loss of exon 5 and in-frame 3-bp deletion at the beginning of exon 8, were identified only at the cDNA level. Their biological significance remains unknown. CONCLUSION: PTT analysis enables examination of long PCR products. The technique is useful for rapid detection of mutations in hereditary breast cancer.
Keywords: zárodečné mutace; Age of Onset; Ovarian Neoplasms; Česká republika; věk při počátku nemoci; geny BRCA1; Adult; dospělí; nádory prsu; polymerázová řetězová reakce s reverzní transkripcí; nádory vaječníků; Czech Republic; Genes, BRCA1; Germ-Line Mutation; lidé; ženské pohlaví; Breast Neoplasms; Humans; Reverse Transcriptase Polymerase Chain Reaction; Female; lidé středního věku; Middle Aged